Advancements in Enteric-coated Microspheres Formulation Development and Mangiferin Drug Delivery for the Treatment of Ulcerative Colitis - Yadav, Swati; Harwansh, Ranjit K.; Mazumder, Rupa (Recent Advances in Drug Delivery and Formulation, 2025)
<span class=
Keywords: ulcer